A Survey of Data Leakage Detection and Prevention Solutions - Shabtai, Asaf.; Elovici, Yuval; Rokach, Lior.; SpringerLink (Online service) (Boston, MA : Springer US, 2012)
Not applicable
Introduction to Information Security -- Data Leakage -- A Taxonomy of Data Leakage Prevention Solutions -- Data Leakage Detection / Prevention Solutions -- Data Leakage / Misuse Scenarios -- Privacy, Data Anonymization, and Secure Data Publishing -- Case studies -- Future Trends in Data Leakage -- References.
Keywords: Computer science; Data protection; Data structures (Computer science).; Information systems; Database management; Computer Science; Systems and Data Security; Data Structures, Cryptology and Information Theory; Database Management; Information Systems and Communication Service